Construção de mosaicos: uma análise por meio de tarefas exploratório-investigativas no 7°ano do ensino fundamental - Miranda, Sílvia Andrea Alexandre (Universidade Federal de São Carlos, 2014)
The present study aimed to analyze how an education that prioritizes tasks of exploratory- investigative nature can contribute to the generation and/or mobilization of geometric concepts in the 7th grade students of elementary school. More specifically, the tasks contained in this dissertation fieldwork, contemplated the learning of geometrical concepts involved in the composition of mosaics with regular polygons. The investigation of a qualitative nature, in the form of case study occurred in a public school in the town of Pilar do Sul, the state of São Paulo, where the information was produced and collected between the first and the second semester of 2013. The technique of triangulation of data involved audio, video and photographs records, students written records and observation notes of the participant teacher - researcher. To describe and analyze the process of students learning we support in Ponte (2009 ) and his various studies on exploratory and investigative tasks, in Fischbein (1993 ) with the theory of figural concepts and Tall (1995); who studied the phases of human activity and mathematical reasoning. The survey results allowed to identify the students progress and difficulties to explore the tasks over time they were performed. With the experiences, the students began to develop clearer written records and used a mathematical language with greater mastery of mathematical terms, in particular the geometry. Furthermore, they demonstrated appropriating and/or expand figural concepts like angles, straight, regular polygons and mobilized such knowledge during the exploration of the properties and relations of these objects.
Keywords: Geometria; Mosaico; Ensino fundamental; Mosaic; Elementary education; Exploratory-investigative tasks; Geometry; Tarefa exploratório-investigativa; CIENCIAS EXATAS E DA TERRA